How prevalent is osteoporosis in a high-risk subgroup? A multicenter study of postmenopausal women hospitalized for fractures in China - Jiang, Jun; Zhou, Yuyang; Chen, Yue; Xiao, Cong; Zhang, Shaoyun; Ma, Xianzhong; Xu, Jinglei; Chen, Ming; Liu, Qixin; Ma, Xiaosheng; Gong, Zhaoyang; Zhang, Peng; et al. (Université d'Ottawa | University of Ottawa, 2026)
Abstract Introduction Osteoporosis is the principal underlying cause of fractures in postmenopausal women. Despite consensus on the importance of secondary prevention, a profound treatment gap exists, partly due to the lack of precise data on disease burden in the highest-risk population. This study aimed to determine the prevalence of osteoporosis and its associated factors specifically among postmenopausal women hospitalized for fractures, a critical evidence gap in orthopedic practice. Methods We conducted a multicenter cross-sectional study across eight tertiary hospitals in China between March and May 2024. Eligible participants were postmenopausal women hospitalized for fractures who met predefined inclusion and exclusion criteria. All participating surgeons completed standardized protocol training for data collection, and each study site contributed up to 160 cases. Results The study included 822 postmenopausal women (mean age: 68.9 ± 10.7 years), with an overall osteoporosis prevalence of 76.9% (95% CI: 73.8%–79.7%). The prevalence was significantly higher among those with longer menopause duration (per year: adjusted odds ratio [aOR] = 1.08, 95% CI: 1.04-1.13, P < 0.001), vertebral fractures (vs patellar, tibiofibular, or ankle fractures: aOR = 3.16, 95% CI: 1.84-5.45, P < 0.001), and a history of fractures (aOR = 8.53, 95% CI: 2.56-52.94, P < 0.001). Conclusions This study reveals an alarmingly high prevalence (76.9%) of osteoporosis among postmenopausal women hospitalized for fractures in China, identifying prolonged menopause, vertebral fractures, and recent fracture history as key risk profiles. The findings mandate a shift in inpatient fracture care. They provide compelling evidence for implementing universal bone health assessment, specifically through in-hospital systems like Fracture Liaison Services (FLS), as a standard of care for this high-risk population to mitigate subsequent fracture risk.

Summary For orthopedic surgeons managing fracture care, this study delivers a pivotal finding: osteoporosis is the underlying condition in over three-quarters (76.9%) of postmenopausal women hospitalized for fractures. The prevalence escalates to over 88% in patients with vertebral fractures or a recent fracture history. This quantifies the immense missed opportunity for secondary fracture prevention at the point of care. The data provide irrefutable evidence for implementing in-hospital systems like Fracture Liaison Services (FLS) and routine DXA screening, moving beyond fracture repair to definitive management of the root cause during the critical inpatient episode.